2012
DOI: 10.1007/s10461-012-0303-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence and Sexual Risk Behaviors Associated with Awareness of HIV Status Among Men Who Have Sex with Men in Paris, France

Abstract: A cross-sectional survey, using self-sampled finger-prick blood on blotting paper and anonymous behavioral self-administrated questionnaires was conducted in Paris in 2009 among MSM attending gay venues. Paired biological results and questionnaires were available for 886 participants. HIV seroprevalence was 17.7 % (95 % CI: 15.3-20.4). Four groups were identified according to their knowledge of their HIV biological status. Among the 157 found to be seropositive, 31 (19.7 %) were unaware of their status and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 47 publications
1
39
1
Order By: Relevance
“…The number of HIV carriers was particularly highly in the 1st district. Our results did not identify the 4th district (Marais) known to be the place where a lot of men having sex with men live, and have a more frequent risk behavior [4]. However, the 1st district is next to the 4th district and, because of their small size, the populations of these 2 districts likely mix frequently.…”
Section: Discussioncontrasting
confidence: 80%
“…The number of HIV carriers was particularly highly in the 1st district. Our results did not identify the 4th district (Marais) known to be the place where a lot of men having sex with men live, and have a more frequent risk behavior [4]. However, the 1st district is next to the 4th district and, because of their small size, the populations of these 2 districts likely mix frequently.…”
Section: Discussioncontrasting
confidence: 80%
“…MSM are also at a high risk of infection with sexually transmitted diseases (STDs) [5,6] because of related risky behaviors, such as having multiple partners and engaging in unprotected anal intercourse (UAI) [7]. Many studies showed that MSM seeking male sexual partners (sampled offline or from fixed venues, such as gay bars, bathrooms, or clubs) engage in several risky sexual behaviors, such as UAI, having multiple sex partners and anal sex [8-12]. However, the studies are limited because offline sampling misses MSM who do not go to these venues due to fear of discrimination, and some HIV-positive MSM who are at high risk for transmission of HIV or STDs may not go to these places either.…”
Section: Introductionmentioning
confidence: 99%
“…1 The disparate impact of HIV and other STIs on MSM as compared to heterosexual men and women reflects both biological [3][4][5] and behavioral 4,6,7 factors. High levels of HIV risk behavior among MSM, and the resurgence of the HIV epidemic in this population, 8 may also be the result of several psychosocial factors, including the changed perception of HIV as a chronic and manageable rather than terminal illness, 9 lack of awareness of HIV status, 10 substance abuse, 11 increased access to and use of testing, 12 condom fatigue, 13 and use of harm reduction techniques including serosorting.…”
mentioning
confidence: 99%